Alienacja i apokalipsa. Sartre i Gombrowicz - Bielecki, Marian (Przestrzenie Teorii, 2024)
The article discusses intertextual relations between Jean-Paul Sartre and Witold Gombrowicz. It concerns both comments of a discursive character in which the polish writer reconstructs the philosophical project of the French philosopher, as well as artistic fabularizations of philosophical concepts in artistic texts.